Антропологія і археогенетика первісного населення України: координація результатів - Потєхіна, І.Д. (Археологія і давня історія України, 2020)
Статтю присвячено результатам міждисциплінарних досліджень населення території України за антропологічними матеріалами з неолітичних могильників Дніпровського Надпоріжжя та поховань трипільської культури. Проводиться аналіз археогенетичних даних, отриманих в результаті секвенування давньої ДНК з цих поховань та їх кореляції з антропологічним контекстом. Висвітлюються витоки антропологічних типів, їхнє генетичне підґрунтя та антропологічні зв’язки первісного населення Північного Причорномор’я. The process of the prehistoric population formation in the territory of Ukraine has become the object of archaeogenetic research in the context of studying the genomic history of Southeast Europe. The work was carried out in the framework of scientific cooperation with the genetic laboratories of Grand Valley State University (USA), Harvard Medical School (USA), Universities of Uppsala (Sweden) and Copenhagen (Denmark). The study of the ancient genome of the Ukrainian population has already yielded results for the Late Mesolithic and Neolithic groups of the Middle and Lower Dnieper, the population of the Trypillia culture of Volhynia (Verteba Cave), as well as for the carriers of Yamna (Pit Grave) Culture and some more late groups of the North Pontic Region (Nikitin, Potekhina et al. 2012; 2017; Potekhina et al. 2013; Krzewińska et al. 2018; Matheison et al. 2018; Potekhina 2016; 2018; 2019; Nikitin 2020). Analysis of mitochondrial DNA from Mariupol-type cemeteries showed the dominance of mitochondrial haplogroup U, which indicates a genetic links with the Mesolithic populations of Scandinavia and the forest belt of Eastern Europe. In some cases, mitochondrial haplogroups H and C have been identified here. The existence of the latter in the Dnieper basin is still difficult to explain, as it is characteristic of eastern Eurasian groups. Genetic studies of the population of the Trypillia culture were carried out on samples dated to 3900— 3500 cal BC from the Verteba cave in Volhynia. The majority of its inhabitants were carriers of the Mt haplogroup H, which connects the people of Trypillia with the Anatolian and Balkan early farmers. This haplogroup was also characteristic of farming cultures of the Central European Neolithic, but its frequency in Verteba is twice as high. The Mt haplogroup U found in one resident of Verteba may indicate contacts with hunters of the steppe Dnieper Region. Genetic polymorphism is also analyzed in the bearers of the Yamna (Pit grave) Culture of the North Pontic Region, which opens a perspective in the context of the Indo-European studies. The research has shown that among the Late Neolithic populations of the proto- European anthropological type with the dominant Mt haplogroup U, and in the early Eneolithic populations of the region, carriers of haplogroup H of the Mediterranean anthropological type appear as a result of contacts with Trypillian groups, which gradually moved in the eastern direction. The same genetic lines in different proportions are preserved in the anthropologically heterogeneous North Pontic population of Yamna Culture. Expanding the analysis of genetic markers of ancient craniological complexes will facilitate the interpretation of the results of archaeogenetic research. Given the historical and anthropological context, they are promising for the study of intercultural contacts and migrations in the early history of the population of Ukraine.